Community Education and Training Transfer: Meaningful Border Crossing? - LaShonda Coulbertson; Rosemary Closson (Adult Education Research Conference, 2010)
Community Health Advisors (CHAs) bridge the health and knowledge gap in marginalized communities. A program was implemented to train CHAs to educate women about their health. The challenges of the transfer of this and similar training is often unreported. The training transfer model serves as the framework for this discussion.